The effect of financial leverage on the cost of financing and the rate of return on equity - محمود فهد عبد علي (Iraqi Journal for Administrative Sciences, 2024)
The current study examined one of the most important financial ratios within the financial function in the establishment, which is the debt ratio or financial leverage and its impact on the cost of financing and the rate of return on equity. This study focused on a problem represented by (the way in which the establishment’s investments are financed and its impact on the profits accruing to the owners and the continuation of profitability in the future). Seeking to achieve a primary goal, which is (knowing the extent of the impact of financial leverage on the cost of financing and the rate of return on equity, and thus guiding business companies to choose the optimal financing structure that reduces the cost of capital to a minimum and achieves a balance between return and risk). Starting from two hypotheses: The rate of return on equity increases with the degree of financial leverage. The weighted average cost of financing decreases with an increase in the degree of financial leverage. To prove its hypotheses, the study relied on the data available in the balance sheets and profit and loss statements of the companies studied. The data was analyzed using a set of financial methods.